DEFENDING FLOOD ATTACKS BY LIMITING PACKET REPLICATION ON TIME INTERVAL (International Journal of Engineering and Computer Science, 2014)
Disruption Tolerant Networks (DTNs) consist of node which has high mobility and lack of consistent in connectivity between the nodes. To adopt such a situation two nodes can only exchange data when they move into the transmission range of each other. DTNs employ such contact opportunity for data forwarding. Due to the limitation in bandwidth and buffer space, DTNs are vulnerable to flood attacks. In flood attacks, attackers inject as many packets as possible into the network, or instead of injecting different packets the attacker’s forward replicas of the same packet to as many nodes as possible. To defend against flood attacks in DTNs A system is proposed in which each node has a limit over the number of packets that it, as a source node, can send to the network in each time interval. Each node also has a limit over the number of replicas that it can generate for each packet. The two limits are used to mitigate packet flood and replica flood attacks